Comprehensive Analyses of the Expression, Genetic Alteration, Prognosis Significance, and Interaction Networks of m6A Regulators Across Human Cancers - Shi, Xiujuan; Zhang, Jieping; Jiang, Yuxiong; Zhang, Chen; Luo, Xiaoli; Wu, Jiawen; Li, Jue (Frontiers in Genetics, 2021)
Accumulating evidences indicate that the deregulation of m6A is involved in various cancer types. The m6A RNA methylation is modulated by m6A methyltransferases, demethylases and reader proteins. Although the aberrant expression of m6A RNA methylation contribute to the development and progression of multiple cancer types, the roles of m6A regulators across numerous types of cancers remain largely unknown. Here, we comprehensively investigated the expression, genetic alterations and prognosis significance of 20 commonly studied m6A regulators across diverse cancer types using TCGA or GEO datasets via bioinformatic analyses. The results revealed that the m6A regulators exhibited widespread dysregulation, genetic alteration and the modulation of oncogenic pathways across TCGA cancer types. In addition, most of the m6A regulators were closely relevant with significant prognosis in many cancer types. Furthermore, we also constructed the protein-protein interacting network of the 20 m6A regulators, and a more complex interacting regulatory network including m6A regulators and their corresponding interacting factors. Besides, the networks between m6A regulators and their upstream regulators such as miRNAs or transcriptional factors were further constructed in this study. Finally, the possible chemicals targeting each m6A regulator were obtained by bioinformatics analysis and the m6A regulators-potential drugs network was further constructed. Taken together, the comprehensive analyses of m6A regulators might provide novel insights into the m6A regulators’ roles across cancer types and shed light on their potential molecular mechanisms as well as helping developing new therapy approaches for cancers.